Newsmaking criminology in the twenty-first century: an analysis of criminologists' news media engagement in seven countries. Issue 2 (2nd April 2020) - Richards, Imogen; Wood, Mark A.; Iliadis, Mary
ABSTRACT: While newsmaking is regularly debated within criminology, few studies have examined why criminologists make news media appearances and how often they do so. Drawing on a dataset of 1211 survey responses and 27 interviews, our study examines these issues, investigating the frequency, predictors and motivations of newsmaking criminology among scholars in seven countries: the United States, United Kingdom, Canada, Australia, New Zealand, Ireland and South Africa. Our findings indicate that gender and career stage are key predictors of criminologists appearing at least once in news media, along with the desire to publicise research, demonstrate research impact, generate university publicity and influence policy and legal reform. Our interview data reveal two central logics informing these predictors: an industrial logic responsive to the demands of academic capitalism and a social logic informing scholars' beliefs on the public role of criminologists and criminological research. On the one hand, our participants' newsmaking practices were driven by moral-political motivations to dispel 'crime news' myths and promote evidence-based criminal justice policies. On the other, they were often also influenced by the imperatives of academic capitalism to promote tertiary education, measure research impact and participate in competitive employment markets.